Marketing Communication Strategy of Halal Tourism in Bandung - Randa, Agrian Ratu; Rengganis, Linangkung Diah Ayu; Santoso, Budi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka Palembang, 2022)
Halal Tourism generally known as new concept of tourism industry that are particularly design for the muslims. Its important to be discussed because the sharia-based economic sector has been growing very rapidly lately, not only in the financial, culinary and fashion sectors but also in the tourism sector where the growth of Middle Eastern tourists is very rapid with a total of approximately 170,000 foreign tourists in 2018 and this figure is projected to increase to 250,000 foreign tourists in in 2019. The purpose of this study was to know how the communication strategy of halal tourism in Bandung. This made the researcher thought that halal tourism is important to be discussed specifically, especially in the Marketing Communication sector, besides its great potential, halal tourism itself requires strong branding so that the process of delivering information and the desires of visiting tourists will be even greater. The result of this study will be focused on Marketing Communication Strategy of Halal Tourism in Bandung. This study used a qualitative research method which the marketing communication strategy of halal tourism in Bandung was described in detail and clearly, then the final results presented the marketing communication strategy model. A case study approach was used in this study, and the validity of the data was tested by using data triangulation based on sources and experts in their fields. This marketing communication strategy is expected to be a reference for the marketing communication strategy of halal tourism in Indonesia.